The effect of depression at work towards employee performance at DNP Consult Sdn. Bhd / Nur Shamsuriati Salleh - Salleh, Nur Shamsuriati (Faculty of Business and Management, 2018)
Environment or condition of the workers at the organization is important for employee performance. Working environment that safe can give comfortable to the employee for working. DNP Consult Sdn. Bhd. is company of construction which is involve in building construction. This study was carried out at 0 P Consult Sdn. Bhd. Other than that, this study also focuses on whether the staff at that company are suffer from depression or stress at work and whether that disaster affect their performance or not. The employee performance has been measured by depression, stress and social environment at work. The sampling technique that has been used in getting sample size is simple random sampling which is 56 populations. This study also has been done by distribute a questionnaire to the staff and collect it back after they had been answer it. After that, it has been run by using SPSS to get a data analysis and getting the finding of the study. The finding for this study is there is relationship between depression at work and also stress to employee performance. But for social environment, there is no significant relationship between it. The result show that the employee at DNP Consult Sdn. Bhd. are having a depression and stress with their work and it a little bit will affect their performance at the workplace. Meanwhile, the social environment did not effect the employee performance. The organization need to pay more attention to this issue because this can contribute to the employee performance at the workplace. The organization can make an event or family day make the staff become more close to each other.